Early perturbation of Wnt signaling reveals patterning and invagination-evagination control points in molar tooth development - Kim, Rebecca; Yu, Tingsheng; Li, Jingjing; Prochazka, Jan; Sharir, Amnon; Green, Jeremy B A; Klein, Ophir D (Development (Cambridge, England), 2021)
Tooth formation requires complex signaling interactions both within the oral epithelium and between the epithelium and the underlying mesenchyme. Previous studies of the Wnt/β-catenin pathway have shown that tooth formation is partly inhibited in loss-of-function mutants, and gain-of-function mutants have perturbed tooth morphology. However, the stage at which Wnt signaling is first important in tooth formation remains unclear. Here, using an Fgf8-promoter-driven, and therefore early, deletion of β-catenin in mouse molar epithelium, we found that loss of Wnt/β-catenin signaling completely deletes the molar tooth, demonstrating that this pathway is central to the earliest stages of tooth formation. Early expression of a dominant-active β-catenin protein also perturbs tooth formation, producing a large domed evagination at early stages and supernumerary teeth later on. The early evaginations are associated with premature mesenchymal condensation marker, and are reduced by inhibition of condensation-associated collagen synthesis. We propose that invagination versus evagination morphogenesis is regulated by the relative timing of epithelial versus mesenchymal cell convergence regulated by canonical Wnt signaling. Together, these studies reveal new aspects of Wnt/β-catenin signaling in tooth formation and in epithelial morphogenesis more broadly.
Keywords: Mesoderm; Wnt Signaling Pathway; Wnt signaling; epitelové buňky; Epithelium; epitel; Morphogenesis; Cell Proliferation; Odontogenesis; Molar; Epithelial Cells; beta Catenin; Epithelial invagination; Mouse; Animals; Tooth development; moláry; odontogeneze; zvířata; myši; proliferace buněk; mezoderm; Mice; signální dráha Wnt; beta-katenin; morfogeneze